If fnx = log log log . . 

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

951.

0π11 + sinxdx =?

  • 1

  • 2

  • - 1

  • - 2


952.

The line x = π4 divides the area of the region bounded by y = sinx, y = cosxand x-axis 0  x π2 into two regions of areas A1 and A2. Then A1, A2 equals

  • 4 : 1

     

  • 3 : 1

  • 2 : 1

  • 1 : 1


953.

The velocity of a particle which starts from rest is given by the following table
t (in sec) 0 2 4 6 8 10
v (in m/s) 0 12 16 20 35 60

The total distance travelled (in metre) by the particles in 10s, using trapezoidal rule is given by

  • 113

  • 226

  • 143

  • 246


954.

If 7x8 + 8x71 + x + x82dx = fx + c, then f(x) = ?

  • x81 + x + x8

  • 28log1 + x + x8

  • 11 + x + x8

  • - 11 + x + x8


Advertisement
Advertisement

955.

If fnx = log log log . . .logx log is repeated n-times, thenxf1xf2x . . . fnx - 1dx is equal to

  • fn + 1 + c

  • fn + 1xn + 1 + c

  • nfnx + c

  • fnxn + c


A.

fn + 1 + c

fnx = log . log . log . . . logx   upto n timesf1x = logxf2x = log logxf3x = log log logxfn - 1x = log log log  . . . . .logx    up to (n - 1) timesNow, xf1xf2x . . . fnx - 1dx=  dxxf1xf2x . . . fnx=  xf1xf2x . . . fn - 1xdtxf1xf2x . . . fn - 1x . t = dtt= logt + c

Put fn(x) = tdtdx = 1fn - 1xf n - 2x . . .f1x . x  dx = xf1x . f2x . . . fn - 1xdt= logfnx +c= fn + 1x + cHence,xf1xf2x . . .fnx - 1dx = fn + 1x + c


Advertisement
956.

If 1 - cosxcsc2xdx = fx + c, then fx is equal to 

  • tanx2

  • cotx2

  • 2tanx2

  • 12tanx2


957.

If In = 0nπ4tanxdx, thenI2 + I4, I3 + I5, I4 + I6, . . . , are in

  • arithmatic progression

  • geometric progression

  • harmonic progression

  • arithmetic-geometric progression


958.

a + xa - x + a - xa + xdx = ?

  • 2sin-1xa + c

  •  2asin-1xa + C

  •  2cos-1xa + C

  •  2acos-1xa + C


Advertisement
959.

If sin8x - cos8x1 - 2sin2xcos2xdx = Asin2x + B, then A = ?

  • - 12

  • - 1

  • 12

  • 1


960.

1 + cos4xcotx - tanxdx

  • - 14cos4x + C

  • 18cos4x + C

  • 14sin4x + C

  • - 18cos4x + C


Advertisement